Autonomy, Centrality, and Persistence in Place: The Indigenous Movement and the Right to the City in Quito. (23rd April 2021) - Rayner, Jeremy
Abstract: This article draws on ethnography with active supporters of the comunas (communes) in Quito to critically engage with the theory and politics of the right to the city. Communal activists—mostly affiliated with the Indigenous movement—forcefully claim rights to the democratic production and appropriation of space advocated by right to the city theorists, as they promote communal self‐management and the authority of communal assemblies over urbanization processes. At the same time, they have had little use for their constitutionally guaranteed right to the city. In carefully laying out the points of convergence between Lefebvrian right to the city theory and communal struggles, I also identify its limits and contradictions, especially: (1) the tension between "the collective power to reshape the process of urbanization" and the fixed forms and meanings of "the city, " and (2) the tension between achieving the "right to centrality" through promoting participation in a concentrated urban center or through the multiplication of centers. A critical theory of urbanization should account for these tensions and for the diversity of political responses to them.